Color change and camouflage in juvenile shore crabs Carcinus maenas - Stevens, Martin; Lown, Alice E.; Wood, Louisa E. (Frontiers in Ecology and Evolution, 2014)
Camouflage is perhaps the most widespread anti-predator defense in nature, with many different types thought to exist. Of these, resembling the general color and pattern of the background (background matching) is likely to be the most common. Background matching can be achieved by adaptation of individual appearance to different habitats or substrates, behavioral choice, and color change. Although the ability to change coloration for camouflage over a period of hours or days is likely to be widely found among animals, few studies have quantified this against different backgrounds. Here, we test whether juvenile shore crabs (Carcinus maenas) are capable of color change for camouflage by placing them on either black or white (experiment 1) or red and green (experiment 2) backgrounds. We find that crabs are capable of significant changes in brightness, becoming lighter on white backgrounds and darker on black backgrounds. Using models of predator (avian) vision, we show that these differences are large enough in many individuals to lead to perceptible changes in appearance. Furthermore, comparisons of crabs with the backgrounds show that changes are likely to lead to significant improvements in camouflage and potentially reduced detection probabilities. Crabs underwent some changes on the red and green backgrounds, but visual modeling indicated that these changes were very small and unlikely to be detectable. Our experiment shows that crabs are able to adjust their camouflage by changes in brightness over a period of hours, and that this could influence detection probability by predators.